FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS KERJA KARYAWAN PANEN KELAPA SAWIT PT.LONSUM (STUDI KASUS: PT. LONSUM KEBUN LIMA PULUH KECAMATAN LIMA PULUH KABUPATEN BATU BARA) - Juita Rahmadani Manik; Nana Trisna Mei br Kabeakan; Rini Susanti (Universitas Quality, 2021)
This study aims to determine whether factors of education, number of dependents, experience, level of income, and age affect the productivity of oil palm harvest workers in PT. LONSUM Lima Puluh Regency of Batu Bara. 2). To find out how much productivity the oil palm harvester labor in PT. LONSUM Fifty Batubara Regency.This type of research is a study case (case study). Simple random sampling technique is a sampling that provides the same opportunity to every member who is in a population to be sampled. Data collection methods are primary data obtained directly from farmers and secondary data obtained from relevant agencies such as offices at PT. LONSUM Fifty. The analysis method used is multiple linear regression analysis.Results of the study 1. From the results of the statistical tests simultaneously it was obtained that the variable number of responsibilities, experience, income and age had a significant or significant effect on the productivity of harvest employees, while the education level variable had no partial effect on the productivity of harvest employees. 2. Partially only the number of dependents, income and age variables significantly influence labor productivity while the variables, education level and experience do not significantly influence employee productivity. 3. It is known that the FFB Production Value / month is 2,646 bunches / month with a total of 26 working days. Then the level of productivity of employees harvested per day is 101 bunches / Hk.